NILAI-NILAI PENDIDIKAN DALAM NOVELET LUKISAN KARYA GOLA GONG (KAJIAN STRUKTURALISME DINAMIK) - Ilmi Solihat (Jurnal Membaca Bahasa dan Sastra Indonesia, 2016)
The purposes of this research are: (1) to reveal value of independent in novellete Lukisan by Gola Gong; (2) to reveal value of creativity in novellete Lukisan by Gola Gong; (3) to reveal of friendship in novellete Lukisan by Gola Gong; (4) to reveal value of social attention in novellete Lukisan by Gola Gong; (5) to reveal value of responsibility in novellete Lukisan by Gola Gong. The researcher used qualitative method with Analisys Content. To reveal values of education in novellete Lukisan by Gola Gong, the researcher used dynamic structuralism study that can define the relation between literature-author-reality of life. The result of this research shows that there is values of education in novellete Lukisan by Gola Gong. Value of Autonomy is described by figure of Tomo who is independent in funding his life and his sister’s education, Rini. Value of creativity is described by figure of Tomo who is creative in making art especially painting. Value of friendship is descibed by the relation of Tomo, Fishermans, and Febri. Tomo is always happy when talking to fishermans, and when Tomo gives advice to Febri about Febri’s Parents who is very protective. Value of social attention is described by Tomo and Fishermans when they help Febri when he is unconscious near Carita Beach. Value of responsibility is more dominant in this novellete, because some figures show their responsibility in their bihaviour. Figure of father and mother of Febri who have responsibility about Febri’s growth. Figure of Mr udin who has responsibility to his job. Figure of Tomo has responsibility to finish his painting for Febri. Figure of Tomo’s parents who have responsibility to their children education, Tomo and Rini, even though their life is not easy. Nowadays, The reality of restriction in relationship between two people who love each other always happen. It is natural for the parents who expect the best for their children’s future. Writer concludes that novellete Lukisan can be teaching material in Senior high school.